ESSAI SUR LA METHODOLOGIE DE L’ENSEIGNEMENT DU FRANÇAIS, LANGUE ETRANGERE DE L’EXIL A TRAVERS L’ETUDE DE CAS CONGOLAIS. METHODE DE P.P.F. - Cédric, ITIYOMBO GEYAYO (IJRDO- Journal of Educational Research, 2022)
According to the theme the example of the school is worth to be mentioned. After many changes and observations in the colonial period, the hope was focused on the coming next. Dayx after the independance with the rebirth of the new methodology that is, the African linguistics. The seventies were the years of optimism on hand for some people and the hopefulness for the other. The old pedant was reduced to silence, but with more respect as regards to his past. The hope was a rude schlock. Every where the pedagogical experiences use to renovate the teaching of French as a foreign language (F.F.L) were reverses and ail the educational project were abandoned in the bad and disastrous conditions. Many things and news teaching methods such as speaking French were neglected and abandoned as well; the old pedant was again promoted and reappeared enthusiastically without speaking of pedagogy and teaching. Besides these failures we joint another which is always there for more than fifty years, that is, five decades since the coming of independences: the study of the African Bantu languages. With exception in some African countries such as Rwanda, Burundi or Mali, the African languages Known as national ones are not used in their schools. To implant French where it must be used according to African or Congolese sociolinguistic realities, withdraw the lessons. From the causes that produced the failure by analyzing then, objectively taking into account the progress of science, to propose some suggestions that fit will, to evoke the reactions of those who are on the field full of their right and responsibility, this is the ambitions intention or purpose of this essay. A careful study of the past experiences can allow preparing the future with the help of today’s researches at by linguistics, those who are his on methods and pedagogues. This is what we try to do as a short study.